PROPHETIC LEADERSHIP AS A LEADERSHIP MODEL IN ISLAMIC EDUCATIONAL INSTITUTIONS - Asriyah, Masfiyatul (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research departs from the need for a leadership model that is able to answer moral, spiritual, and managerial challenges in Islamic educational institutions. In this context, prophetic leadership is seen as an ideal paradigm because it is rooted in the prophetic values ṣidq (honesty), amānah (responsibility), tablīgh (communicative), and faṭānah (intelligence) that lead leaders to act as moral guides as well as organizational drivers. The purpose of this research is to analyze the role and implementation of prophetic leadership as a leadership model in Islamic educational institutions, as well as how its values can be applied in modern education management. The research method used is library research with a descriptive qualitative approach, referring to the theories put forward by Kuntowijoyo, Al-Attas, Qomar, Bass, and Greenleaf. The results of the study show that prophetic leadership is able to integrate spiritual values with work professionalism through the application of the principles of transcendence, humanization, and liberation in institutional vision, human resource management, organizational culture, and the development of Islamic education curriculum. In conclusion, the prophetic leadership model is not only relevant to strengthen the character of Islamic educational institutions, but also effective in creating a management system that is just, value-oriented, and adaptive to the changing times, thereby contributing to the formation of a generation with noble character and global competitiveness.